2013
DOI: 10.1103/physrevb.87.020503
|View full text |Cite
|
Sign up to set email alerts
|

Vortex-induced strain and magnetization in type-II superconductors

Abstract: It is argued that the stress caused by vortex cores in the mixed state of superconductors may result in a field dependent contribution to the free energy and magnetization of measurable levels. For sufficiently strong stress dependence of the critical temperature, ∂Tc/∂p, this contribution may result in the so-called "second peak" in the field dependence of the reversible magnetization, the effect often masked by vortex pinning and creep.PACS numbers: 74.20. De,74.25.Ha,74.25.Wx,74.62.Fj The so-called secon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Recently, it has been shown that stress induced intervortex interaction can lead to square vortex lattice in tetragonal superconductors 38 . Such a coupling between crystalline elasticity and superconductivity can be treated using the dependence of T c with pressure, dT c /dP 36,[39][40][41] . Generally, with dT c /dP > 0, vortices are repelled from places with internal stress and the opposite occurs with dT c /dP < 0.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that stress induced intervortex interaction can lead to square vortex lattice in tetragonal superconductors 38 . Such a coupling between crystalline elasticity and superconductivity can be treated using the dependence of T c with pressure, dT c /dP 36,[39][40][41] . Generally, with dT c /dP > 0, vortices are repelled from places with internal stress and the opposite occurs with dT c /dP < 0.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kogan et al . 17 the strains in this type of composite system arise due to the difference in density of the normal (i.e. InBi) and superconducting (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…A vortex can perturb the strain field of the crystal that induces additional interactions between vortices [12][13][14][15][16][17]. In a simple picture, nucleation of the normal vortex core which has a different density than the surrounding superconductor, induces a strain field.…”
Section: Introductionmentioning
confidence: 99%